Teacher learning in an inquiry community: A case study at a private higher education institution in Malaysia / Ann Rosnida Md Deni - Ann Rosnida, Md Deni (2015)
The purpose of this study was to view the feasibility of an alternative staff development, the teacher inquiry community (TIC) as a worthwhile effort to improve university teachers’ practice. The study, conducted at a Malaysian private higher education, aimed at understanding situated processes within the TIC, factors that influenced these processes, and the effects of participation on university teachers and their practice. The study adopted the qualitative case study approach and employed the situated learning theory as its theoretical framework. Data for the study was collected through participant observation, analysis of audio-recorded interactions and classroom artifacts, researchergenerated documents, and interviews. The TIC project was carried out in three consecutive cycles within a period of one year. Eight English language university teachers took part in the first cycle, ten in the second and nine in the last cycle. Throughout the three cycles, thirty weekly meetings were held to understand and solve various instructional problems shared by the participants. A protocol was employed to guide interactions and discussions within the TIC. The study finds that the processes within the TIC were complex. Various activities were identified occurring at group and individual levels. Group-level activities involving collective reflection, inquiry, and negotiation of knowledge shared, promoted the generation of a wide variety of knowledge which was then processed by individual teachers through reflection and/or experimentation on practice. Processes identified were affected by various factors within the TIC (the protocol, community members, tools, instructional dilemmas shared); individual teachers (attitude, beliefs, teaching and learning experiences, confidence level, external circumstances, biological factors, skills to reflect on practice) and teachers’ workplace (time, administrative work, shared/sole responsibilities, teaching allocation, system imposed). As a result, teachers’ participation led to varied effects on teachers and their practice. The study finds that the TIC has a potential to be a worthwhile staff development as teachers’ participation improved their pedagogical knowledge and understanding of their own practice and general aspects concerning students, teaching and learning. Most importantly, some teachers made adjustments to their beliefs about students, teaching and learning and ways they taught certain language skills and their handling of problematic students within their classrooms. The study extends understanding on the complex processes occurring within the TIC; the needs for sustainability and continuity in teacher learning; the supportive functions of various tools and varied input on teacher learning; the characteristics of people that would make TIC work, and how different contextual factors affected teacher learning and outcomes. The findings of this study have some implications for implementations of TIC within higher education. Formations of TICs in higher education requires revision of policies governing the scope of staff development; the reward and evaluation system; and the definition of success. The findings of the study also have implications on the recruitment and new responsibilities for staff developers in managing and facilitating learning in a TIC, recruitment of community members, and management of TICs within higher education institutions.